A scientometric investigation on the impact of the PhyloCode proposal on the scientific literature - DANIEL C. SCHELESKY-PRADO; RAFAELA L. FALASCHI; IGOR P. AFFONSO (Anais da Academia Brasileira de Ciências)
Abstract In 2000, the first draft of PhyloCode was made public, an alternative naming code that does not follow Linnaean rankings and is based on the phylogenetic relationships of taxa in cladograms. In this study, the impact of the PhyloCode on scientific literature was analyzed from its first appearance in the literature to 2021. We investigated the areas that have most assimilated the proposal, the criticisms that have arisen over time, and whether there has been growing adherence to it up to the present day. The analyzed data were obtained from the Clarivate Analytics Web of Science database, where 121 articles that used or discussed the PhyloCode were found. Initially, there was an increase in publications, but in mid-2004, there was a downward trend, which was more noticeable after 2008. Results suggest that despite the criticisms, the proposal has been used in research in several areas, mainly in Zoology and Botany, as an alternative to the Linnaean ranking system. Most articles have been published in Systematics and Taxonomy and discuss the functionality of the proposed code. Despite the proposal’s potential, its acceptance can be considered relatively low and it still generates discussions, just like any scientific novelty.